Teaching communicative competence to students of the bachelor’s degree in Preschool Education - León Arellano, Esperanza (Rastros Rostros, 2021)
Introduction: Pragmatic competence is problematic for students in the pre-school education course, amongother reasons because the communication situations presented by the teachers do not meet the requirementsfor them to demonstrate their skills.Metodology: In the present research, it was designed and applied an intervention strategy through learningsituations that would allow students to argue with clarity and congruence by developing two types of products:a lecture (written) and a documentary (oral), which in cognitive terms demand the same skills, as well as theuse of linguistic records and prototypical gender nomenclature. A case study was carried out, in which 24second semester students participated.Results: The results suggest that planning, argumentation and organizational skills can be favored in bothproducts, however, in metacognitive aspects there are still areas of opportunity.Conclusions: Finally, the work provides recommendations in relation to the design of the evaluation instruments, in the sense of identifying from the beginning data related to cognitive processes and rhetorical movements typical of the products, as well as in aspects that must be taken into account when designing learningsituations and communicative situations.
Keywords: writing; higher education; professional competence